Lifestyle profile and prevalence of Burnout Syndrome in health students at a private university in Santarém-PA during the Covid-19 pandemic: a cross-cutting study (Research, Society and Development, 2021)
Objective: to verify the lifestyle profile and the prevalence of Burnout Syndrome in university healthcare students during a COVID-19 pandemic. Methodology: This is an observational epidemiological study, descriptive and cross-sectional, with 272 university students in the health area. As data collection instruments, we used the Individual Lifestyle Profile Questionnaire (PEVI), the Maslach Burnout Inventory and the sociodemographic questionnaire. Results and discussion: There was a higher proportion for the “positive” classification in the physical activity, preventive behaviors, social relationship and stress control components, as well as the “intermediate” classification for the nutrition component. In the overall result of the individual lifestyle profile, students were classified as “intermediate” (44.1%), followed by “positive” (41.5%) and “negative” (14.3%). In the Burnout dimensions, students with a low level of “emotional exhaustion” (51.8%), a high level of “disbelief” (55.9%) and a low level of “professional fulfillment” (100%) prevailed. The relationship between the occurrence of Burnout and the lifestyle profile indicated the presence of Burnout (n=14), prevalent in the “intermediate” profile (42.9%). Conclusion: The study reveals the need for greater investment in prevention and awareness of the academic community for the adoption of a healthy lifestyle. It is suggested to carry out more comprehensive studies on the subject, which serve as evidence for the development of interventionist measures, both in the academic sphere and in public policies to promote the health of university students.